2010
DOI: 10.4103/0378-6323.60570
|View full text |Cite
|
Sign up to set email alerts
|

Blue rubber bleb nevus syndrome: Prominent oral findings

Abstract: Blue rubber bleb nevus syndrome is a rare disorder characterized by multiple cutaneous venous malformations in association with visceral lesions, most commonly affecting the gastrointestinal tract. Oral cavity lesions occur in 59 to 64% of cases. We report a unique presentation of this syndrome in a 25-year-old male patient with prominent oral findings. This is a sporadic case, started during early childhood, progressively increasing in number and size. Oral vascular lesions were part of gastrointestinal invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…5 Oral lesions are very common and occur in 59-64% of cases, mostly in the buccal mucosa, ventrolateral tongue, and retromolar trigone. 2 There are a wide variety of treatment strategies for symptomatic oral lesions. Smaller malformations can be treated with sclerotherapy, surgical excision, lasers, radiation therapy, electrodessication and curettage, and cryotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5 Oral lesions are very common and occur in 59-64% of cases, mostly in the buccal mucosa, ventrolateral tongue, and retromolar trigone. 2 There are a wide variety of treatment strategies for symptomatic oral lesions. Smaller malformations can be treated with sclerotherapy, surgical excision, lasers, radiation therapy, electrodessication and curettage, and cryotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…3 Embolization using sclerosing agents is highly efficacious and poses no risk of hemorrhage, and for this reason is considered by most physicians to be the first-line therapy. 2,3 Sclerosing agents commonly used include 5% ethanolamine oleate, 5% sodium morrhuate, 1% polidocanol, sodium tetradecil sufate, and hypertonic saline. 2,3 In a study performed on 30 patients with oral vascular lesions, the authors found that ethanolamine oleate was 100% effective in relieving symptoms and there were no serious adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations